Performance of microvesicles as biomarkers of clinical outcome in sepsis and trauma: A pilot study - Puga, Marcelo Lourencini (2022)
Division of Intensive Care. Department of Surgery and Anatomy. Ribeirão Preto Medical School. University of São Paulo. Ribeirão Preto, SP, Brazil